Diagnostic tools for allergic rhinitis and asthma - Baççıoğlu Kavut, Ayşe; Kalpaklıoğlu, Füsun (ENT Updates, 2012)
The diagnosis of allergic airway diseases is based on symptoms, and the laboratory tests help us to classify the types. A correct diagnosis is important, since the treatment will change in different types of diseases. For example, untreated rhinitis may result in other diseases like asthma, and deteriorate the quality of life. Therefore, early diagnose of allergic airway diseases is important before the disease progresses. This review summarizes the currently known diagnostic tools which can be useful in daily practical life and researches, including assessment of symptoms, physical examination, allergy skin tests, total and specific IgE, nasal provocation test and assessment parameters (symptoms, nasal flow and secretions), nasal mucosal sampling, and pulmonary function test.